Health Benefits, Associated Disorders and Influencing Factors of Gut Microbiota: A Comprehensive Review - Ali, Zeeshan; Saeed, Sumaira; Mehdi, Bushra Jabeen; Ahmed, Hafsa; Hussain, Syed Ashiq; Bashir, Naila; Ashfaq, Javaria; Muzamil, Muhammad; Zahoor, Muhammad Aftab; Ali Khan, Muhammad Asad; Noor-Ul-Huda (Indus Journal of Bioscience Research, 2025)
The gut microbiota considered as the diverse community of the microorganisms that found within the gastrointestinal tract. It plays a significant role and provides health benefits to the body in various processes including mental, digestive and metabolic health. This review article highlighted and elaborated the gut microbiota composition, factors affecting on the gut microbiota essential for the metabolic health of body and its brief beneficial role for the human body and also discussed the diseases associated with the gut microbiota in detail. It is also considered that gut microbiome plays a beneficial role in maintaining and improving the overall health of body by employing various mechanisms such as synthesis of vitamins, development and production of short chain fatty acids (i.e., SCFA) and breakdown of the carbohydrates considered as complex. These all factors exhibit healthy role maintenance and regulation of gut associated barriers, improving immunity and fat metabolism system. The disturbance in microbial community of gut leads to gastrointestinal, metabolic and neurological disorders. Different factors such as life style, diet and exercise significantly shapes the gut microbiota which helps in designing personalized therapeutic strategies to prevent life threatening diseases. This review depicts detailed literature on the relation of gut microbiome with the body health.